Early Immunomodulatory Effects of Different Natural Surfactant Preparations in Preterms With Respiratory Distress - Yalaz, Mehmet; Tanriverdi, Sema; Uygur, Özgün; Altun Köroğlu, Özge; Azarsiz, Elif; Aksu, Guzide; Kültürsay, Nilgün (Frontiers in Pediatrics, 2022)
Background: Respiratory distress syndrome (RDS) is the most common respiratory disease in premature infants. Exogenous natural surfactant preparations are used in the treatment of RDS. In recent years, it has become increasingly evident that surfactant plays an immunoregulatory role. Objectives: The aim of this study was to evaluate cytokine and chemokine response following three different regimens of natural surfactant treatment in preterm newborns with RDS. Methods: Premature newborns below 32 weeks of gestation who were intubated for RDS and given early surfactant rescue therapy were included in the study. Newborns were randomly divided into three groups and Beractant 100 mg/kg (B-100), Poractant alfa 100 mg/kg (Pα-100) and Poractant alfa 200 mg/kg (Pα-200) were administered intratracheally. Blood samples and transtracheal aspirates (TA) were collected just before and 4-6 hours after the surfactant treatment. Total eosinophil count, inducible T Cell alpha chemoattractant (ITaC), macrophage inflammatory protein 3 beta (MIP3b), interleukins (IL) 5, 8, 9, 10, 13, immunoglobulin E (IgE), interferon gamma (IFN-γ), eotaxin and tumor necrosis factor beta-1 (TGF-β1) were measured from blood and tracheal aspirate samples. Results: A total of 45 infants, 15 in each group, were included in the study. Mean gestational age, birth weight, antenatal, demographic and clinical characteristics of the study groups were similar. IFNγ concentration and eosinophil counts in TA decreased after surfactant replacement in all groups, especially in the infants treated with Pα-100 and Pα-200. Eotaxin, TGF beta and IL-8 concentrations in TA increased significantly in the infants treated with Pα-100 and Pα-200. IL-9 levels in TA decreased in the B-100 group but increased in the Pα-100 and Pα-200 groups. Blood levels of cytokines and chemokines showed significantly decreased levels of ITaC and MIP3b only in the B-100 group, but no significant change was observed in the Pα-100 and Pα-200 groups. Conclusion: In our study, the different immunomodulatory effects of natural surfactant preparations on newborn lung is proven. We found that Poractant α, one of the natural surfactant preparations, shifted the lung immune system towards TH2.